Biblijny Lewiatan – realnie istniejące zwierzę czy mityczny potwór morski? - Mielnik, Dawid (Verbum Vitae, 2017)
The main purpose of the paper is discovering whether Leviathan in the Hebrew Bible is a real animal or a mythic marine monster. A definitive answer is in fact possible, thanks to analysis of certain biblical fragments where the crucial term is present. The paper is divided into two main parts: First, Leviathan is examined as encountered within extra-biblical literature. In the second part, this creature is analyzed in the context of concrete biblical fragments which include a presentation of Leviathan. On the basis of research, it can be claimed that, in the Hebrew Bible, Leviathan is to be understood as a mythic marine monster. Conversely, there is no known fragment in which Leviathan has to be understood as a real animal.